Polymorphisms in some proinflammatory genes (TNFα and β, IL-1β, IL-6, ADAM17) in severe chronic venous disease - Slonková, Veronika; Vašků, Anna; Vašků, Vladimír (Journal of the European Academy of Dermatology and Venereology, 2023)
BACKGROUND: Chronic venous disease (CVD) is a common disorder of lower extremities. OBJECTIVES: The study was scheduled to investigate the relationship between polymorphisms in major proinflammatory genes TNF α (-238 A/G; -308 A/G), TNF β (NcoI), IL-1β (+3953 T/C); IL-6 (-174 G/C; -596 G/C) and ADAM17 (3'TACE) and CVD risk. Genotype-phenotype study was calculated to test possible association between examined genotypes and phenotypes of CVD. METHODS: Finally, 150 CVD patients and 227 control subjects were enrolled to the study. Genotypes in proinflammatory gene polymorphisms were identified from isolated DNA by PCR method and restriction analysis. RESULTS: Significant differences in genotype distribution/allelic frequencies in TNF β gene, IL-1 β gene and in ADAM17 gene polymorphisms were found between CVD women and control ones. In the genotype-phenotype study, identified genotypes were associated with arterial hypertension (ADAM17, IL-6-men), ischaemic heart disease (TNF α and β genes), diabetes mellitus (ADAM17-women, TNF β-men), age of CVD onset (TNF α and IL-6), ulceration (ADAM17), duration of ulceration (ADAM17), ulceration recurrence (ADAM17-women), home care necessity (TNF α), varices surgery (TNF α), erysipelas development (ADAM17-men) and tumour development (TNF α). CONCLUSION: Studying of these polymorphisms associations can help us better identify patients at higher risk of developing severe CVD.
Keywords: kardiovaskulární nemoci; Polymorphism, Single Nucleotide; Interleukin-1beta; Humans; lymfotoxin-alfa; Chronic Disease; jednonukleotidový polymorfismus; Female; Interleukin-6; frekvence genu; Genotype; lidé; TNF-alfa; ženské pohlaví; Cardiovascular Diseases; interleukin-6; interleukin-1beta; chronická nemoc; protein ADAM17; Genetic Predisposition to Disease; genetická predispozice k nemoci; Gene Frequency; Tumor Necrosis Factor-alpha; genotyp; ADAM17 Protein; Lymphotoxin-alpha